Determining the non-traditional exports in Perú 2002 - 2015 - Bustamante Romaní, Rafael (2015)
In the present study is estimated a function of demand for non- traditional exports for Peru multivariate analysis using multivariate cointegration, which examines the existence of a long-term relationship between non-traditional exports, external demand, domestic demand is estimated, the level of employment and the rate of the bilateral and multilateral real change. The results show that foreign demand plays a significant role in the determination of non-traditional exports in Peru. Similarly, the bilateral and multilateral real exchange rate also significantly affect the demand for nontraditional exports. The interpretation of the respective elasticities comprises obtaining the same from cointegration.